Optimizing the Principal's Visionary Leadership Through the Integration of SWOT and TOWS Analysis in Building an Innovative Culture to Achieve the School's Vision and Mission - Wulan Roudhotul Nasikhah; Burhanuddin Burhanuddin; Agus Timan (Dinasti Publisher, 2025)
This research aims to determine: (1) the principal's strategy in developing an innovative culture that is integrated with the school's vision and mission; (2) integration of SWOT and TOWS analysis in building an innovative culture in the school environment; and (3) the principal's strategic plan in implementing visionary leadership to strengthen an innovative culture that is integrated into the school's vision and mission. This research uses a qualitative approach with a case study type of research. Data collection techniques use interviews, observation and document study. The research results show that: (1) the school develops an innovative culture that is integrated with the vision and mission through SWOT and TOWS analysis, by utilizing religious-based strengths and increasing the variety of learning methods that are more participatory; (2) the integration of SWOT and TOWS analysis allows schools to formulate effective strategies to build an innovative culture by exploiting strengths and opportunities, overcoming weaknesses, and facing threats in an effort to improve the quality of education and school reputation; and (3) the school principal's strategic plan for the next five years is prepared based on SWOT and TOWS analysis which aims to improve the quality of education and build an innovative culture through an integrated approach and visionary leadership, by integrating the components of the school management team to achieve the school's vision of producing qualified graduates. excellence, character, and ready to face the challenges of the world of work and social life.